Right to Education and Out-of-School Children: Development of an Exemplar Bridge Course - Sanwal, Suniti (THE PRIMARY TEACHER, 2018)
The Right to Education Act (RTE) 2009, guarantees free and compulsory education for children between 6–14 years of age in India. The RTE Act also makes a provision for providing special training to those children who may have either never enrolled in school, or may have dropped out of the school system. In order to bridge their learning gaps, a bridge course is being developed. This article discusses the process of development of an exemplar bridge course. To understand the issues and challenges of Out-of-School Children visits were made to the Special Training Centers (STC) of two Indian states, Gujarat and Delhi, which provided special training to out of school children for bridging their learning gaps so that they can be mainstreamed into age-appropriate classes. The study draws a comparison of the curriculum, teacher qualifications, salary, training and classroom arrangements in the STCs of these states. Drawing lessons from the visits, the article highlights the gaps and how they were taken into account while designing the bridge course. The bridge course has been divided into four levels, (barring level I, which is a readiness level), each having a diagnostic test, three competency stages and an assessment test. The author makes some recommendations for the STCs based on field experiences.